P84 'I am not fixed;' A qualitative study exploring the views about respiratory care of people born with OA/TOF. (11th November 2022) - Bray, L; Gray, V; Cullis, P; Gorst, S; Faulkner, J; Thursfield, RM
Abstract : Introduction and Objectives: Approximately 1 in every 4100 people worldwide are born with oesophageal atresia ± tracheo-oesophageal fistula (OA/TOF). Whilst surgical correction is, in most cases, performed within the early years, physiological dysfunction remains. The care of this group of people is disparate with no clear guidance or referral pathways outside of surgical management. With reflux and aspiration being commonly seen, respiratory symptoms are frequently encountered and often misdiagnosed. This qualitative study embedded within the ocelot study (https://tofs.org.uk/ocelot-study/ ), which seeks to determine a core outcome set for this patient population, explored the experiences of adults and children of living with OA/TOF. Methods: Five focus groups and five individual interviews were conducted via video conferencing software. The groups were facilitated by clinicians, researchers and Tracheo-Oesophageal Fistula Support (TOFS) charity leads. Participants were invited through the national TOFS charity and included individuals born with OA/TOF, or a parent of a person born with OA/TOF. A topic guide shaped the focus group discussion, but the group conversation was open and free. Data were transcribed, coded, themes identified and discussed within the team. Results: Participants included 12 adults with OA/TOF and 6 family members and four children with OA/TOF (aged 7–14). Despite varying ages and backgrounds, similar themes were common throughout. The participants, regardless of age continued to face daily challenges with respiratory symptoms. They reported a misconception, particularly from general health care services, that they had been 'fixed at birth' and therefore no longer should experience symptoms related to their OA/TOF. Participants' lives were disrupted by having to make alterations to their life to allow for eating difficulties, persistent sleep issues, breathlessness, and chest infections. Conclusions: The level of ongoing disruption to life experienced by these participants was surprising to the clinicians on the team. There are indications that routine follow up beyond the paediatric years and altering the medical terminology, which implies someone has been fixed, may help to recognise the ongoing nature of any of the respiratory symptoms associated with this anatomical abnormality. Further work is required to develop an agreed lifelong standard of care for this group of patients. Please refer to page A214 for declarations of interest related to this abstract.